Modeling Islamic Social Reporting in the Indonesian Capital Market - Muhammad Adnan; Fithriady Fithriady; Marwiyati Marwiyati; Rahmi Rahmi (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
Islamic Social Reporting (ISR) is an extension of the social reporting concept that examines companies' spiritual and economic roles. However, some Sharia-indexed companies in the Indonesian Capital Market do not fully disclose ISR in their annual reports, despite its importance for Muslim investors. This study analyzes the impact of company size, age, profitability, leverage, and independent commissioners on ISR disclosure using panel data regression analysis. The research employs a quantitative approach, utilizing secondary data from a panel dataset consisting of 10 companies listed on the Jakarta Islamic Index (JII) from 2016 to 2022. To analyze the data, this study utilizes panel data regression analysis, which incorporates three distinct approaches: the standard effect model, fixed effect model, and random effect model. The Chow Test and Hausman Test are then conducted to determine the optimal model for estimating the outcomes. The panel regression results are subsequently estimated utilizing the Random Effect Model approach. The findings indicate that company size, profitability, leverage, and independent commissioners do not affect ISR disclosure. However, company age significantly and positively influences ISR disclosure. These results emphasize the need for mandatory ISR disclosure regulations in the Indonesian Capital Market to enhance transparency and accountability for Muslim investors.======================================================================================================== ABSTRAK – Pemodelan Islamic Social Reporting di Pasar Modal Indonesia. Islamic Social Reporting (ISR) merupakan perluasan dari konsep social reporting yang tidak hanya membahas peran perusahaan dalam perekonomian, tetapi juga perspektif spiritual. Akan tetapi, walaupun ISR merupakan informasi penting bagi investor muslim dalam pengambilan keputusan investasi, beberapa perusahaan dalam indeks syariah belum sepenuhnya mengungkapkan ISR dalam laporan tahunannya. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh ukuran perusahaan, umur perusahaan, profitabilitas, leverage dan komisaris independen terhadap pengungkapan ISR di Pasar Modal Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan data sekunder berbentuk data panel dari 10 perusahaan yang listing di Jakarta Islamic Index (JII) dari tahun 2016-2022. Data dianalisis dilakukan dengan regresi data panel yang menggunakan tiga pendekatan: common effect model, fixed effect model dan random effect model. Uji Chow dan Uji Hausman digunakan untuk memilih model terbaik dalam mengestimasi hasil penelitian. Sementara itu, untuk mengestimasi hasil regresi panel digunakan pendekatan Random Effect Model. Hasil penelitian menunjukkan bahwa ukuran perusahaan, profitabilitas, leverage dan komisaris independen tidak berpengaruh terhadap pengungkapan ISR di Pasar Modal Indonesia, sedangkan umur perusahaan berpengaruh positif signifikan terhadap pengungkapan ISR di Pasar Modal Indonesia. Implikasi dari temuan ini menitikberatkan pada pentingnya regulasi tentang kewajiban pengungkapan ISR bagi perusahaan-perusahaan yang listing di JII agar meningkatnya transparansi dan akuntabilitas untuk para investor Muslim.